Healthcare Access and Utilization in Rural Communities of Indonesia - Nabila Anggraini (PSPP JOURNALS, 2023)
In this research, look at how people in Indonesia's rural areas gain entry to and make use of medical treatment. 500 households were randomly selected from four rural villages in Central Java for a cross-sectional study. High rates of unmet healthcare needs and low healthcare utilization rates were found to suggest that healthcare access and utilization are poor in rural regions of Indonesia. Distance, cost, and a dearth of services are all factors that limit people's ability to receive medical treatment when they need it. Healthcare access and usage were also found to be significantly influenced by socioeconomic status, education, and health literacy. Conclusions Significant efforts should be made to increase healthcare access and utilization in Indonesia's rural regions, according to the results.